Rock ballad in Ukrainian music - Vavshko, Iryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
The relevance of the research is explained by the fact that the genre of a rock ballad is a very common and popular but at the same time little-studied phenomenon in a complex genre system of rock music. The purpose of the research is to consider the peculiarities of theimplementation and evolution of this genre in the Ukrainian rock music through the lensof typical genre parameters (genre poetics) formed in the works of British, American andWestern European rock bands. The research methods are the determination of the peculiarities of the music poetics of the Ukrainian rock ballad (at the level of the compositional pattern – introduction, verse and bridge) by means of comparative and parametric analysis. The main results and conclusions of the research. Work of the most Ukrainian rock bands and their stylistics moved in the following directions: borrowing and implementing the traditions of Western European and British rock bands, as well as continuing the line of a pop Ukrainian song with adaptation to rock culture and individual sound of each band. Even a parametric overview of the most famous rock ballads of Ukrainian rock bands – “Braty Gadiukіny”, “Mertvyi Pіven”, “Plach Yeremii” and “Ocean Elzy” vividly shows the overall picture of the development of the genre. If the work of the rock bands of the 90s more closely resembles Western counterparts, then the rock ballads of the 2000s are predominantly drawn to pop-rock style. In the process of analyzing the compositional patterns of the national rock ballads, we come to the conclusion that the poetics of the genre here gets a bright, individual implementation, while retaining the typical genre invariant. The significance of the research is associated with the ability to partially close the existing gaps in the study of the characteristics of national rock music, as the question of the music poetics of the Ukrainian rock ballad is first presented in national musicology.